The Influence of the Political System on Education Curriculum Policy in Indonesia - Agustina Haryani Putri; Suhardi Suhardi (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research aims to describe the literature review on the influence of politics on changes in education curriculum policy in Indonesia from 2004-2013. This research method employs a qualitative approach with a literature review framework. The research process entails gathering articles, filtering them, presenting them, engaging in discussions, and drawing findings.   The primary sources of research data include books, journals, and national articles published during the past seven years.   The findings indicated that out of ten articles, four were relevant to the topic of discussion.   The curriculum underwent several revisions following the reform era in 1998. These changes included the implementation of the Competency-Based Curriculum in 2004, the introduction of the Education Unit curriculum in 2006, and the adoption of the 2013 curriculum.   Curriculum revisions in Indonesia are frequently influenced by the prevailing political system as a way to demonstrate leadership authority during that period.   Therefore, curriculum modifications are not grounded on educational requirements.